In search of project excellence: a systems approach of triangulation in a mixed methodology empirical research. (4th June 2010) - Basu, Ron
The majority of major projects are criticised for having failed their perceived quality objectives. This study explores the dimensions and constructs contributing to the project quality and sustainable outcomes leading to project excellence focusing on the efficacy of methodological triangulation in this research. A mixed methodology of semi-structured interviews followed by an online questionnaire survey, a partial least squares (PLS) analysis and two UK infrastructure case studies (Terminal 5 and High Speed 1) were applied. A systems approach supported by the methodological triangulation process has been applied to the mixed methodology of both quantitative and qualitative research approaches. The research contributed to the definition of project quality underpinned by three dimensions of design, process and organisation. Three propositions in search of project excellence were tested and two propositions were fully supported and one was partly supported by research results and strengthened the approach of methodological triangulation and systems thinking.